Evolución de percepciones estratégicas: EE.UU.-Vietnam, de la ficha de dominó al peón de ajedrez - Herrero, Rubén (UNISCI Discussion Papers, 2007)
This article shows the evolution of the U.S. strategic perceptions of Vietnam, since before the Vietnam War, until 2007. Briefly, in the text, the main doctrinal principles ruling this evolution are examined: namely, the Eisenhower doctrine; the Cold War paradigm (mainly followed by the Kennedy and Johnson Administrations); Kissinger’s pentapolar diplomacy, which shaped the Nixon Administration foreign policy; and last, the unlocking of the relations between both countries twenty years after the war and the role of Vietnam in the George W. Bush Administration’s war against terrorism.